A Study of Noun Phrase Awareness at the Eighth Graders of Two Islamic Junior High Schools in Makassar - Awaluddin Syamsu (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2021)
Syntactic awareness has been linked to reading comprehension skills. In Junior high schools, syntactic awareness of noun phrases can be very important for the students in the Indonesian context because it can improve their reading comprehension. However, teaching noun phrases for the students can be challenging due to the grammar difference. The junior high school student’s noun phrase awareness was measured using a developed test. It consists of 28 questions with seven noun categories. The reliability test was conducted using KR-20 and the result was .90. The study indicated the average score of the students was 69.07 (fair). Of the seven noun phrases category, nominal possessors and conjoined noun phrases were good, prenominal possessors, multiple genitive constructs, alienable and inalienable possessions, and ad-positional phrases were fair, and nonreferential generative was weak. Referring to the result of the research, it is suggested to improve the student’s noun phrase awareness to enhance their reading comprehension.